Modelling inter-regional trade flows: data and methodological issues in Rhomolo - Olga Ivanova; D'Artis Kancs; Dirk Stelder (European Regional Science Association (ERSA), 2010)
The present paper studies the modelling of inter-regional trade flows in the newly developed general equilibrium model of European Commission, Rhomolo. In contrast to international trade, usually, trade of goods and services between regions is not recorded statistically. As a result, no statistical data exists for inter-regional trade, which could be readily used for modelling purposes. We propose an augmented entropy approach, which combines the Transtools model's inter-regional trade and inter-regional transport cost data with data from regional and national statistics to obtain a full set of balanced bilateral trade data for all inter-regional transactions.
Keywords: C68; F10; F15; F17; R11; R41; 330; Inter-regional trade; general equilibrium; trade costs; entropy